Standing genetic variation in laboratory populations of insecticide‐susceptible Phlebotomus papatasi and Lutzomyia longipalpis (Diptera: Psychodidae: Phlebotominae) for the evolution of resistance - David S. Denlinger; Spencer B. Hudson; Nadya S. Keweshan; Zachariah Gompert; Scott A. Bernhardt (Evolutionary Applications, 2021)
Abstract Insecticides can exert strong selection on insect pest species, including those that vector diseases, and have led to rapid evolution of resistance. Despite such rapid evolution, relatively little is known about standing genetic variation for resistance in insecticide‐susceptible populations of many species. To help fill this knowledge gap, we generated genotyping‐by‐sequencing data from insecticide‐susceptible Phlebotomus papatasi and Lutzomyia longipalpis sand flies that survived or died from a sub‐diagnostic exposure to either permethrin or malathion using a modified version of the Centers for Disease Control and Prevention bottle bioassay. Multi‐locus genome‐wide association mapping methods were used to quantify standing genetic variation for insecticide resistance in these populations and to identify specific alleles associated with insecticide survival. For each insecticide treatment, we estimated the proportion of the variation in survival explained by the genetic data (i.e., “chip” heritability) and the number and contribution of individual loci with measurable effects. For all treatments, survival to an insecticide exposure was heritable with a polygenic architecture. Both P. papatasi and L. longipalpis had alleles for survival that resided within many genes throughout their genomes. The implications for resistance conferred by many alleles, as well as inferences made about the utility of laboratory insecticide resistance association studies compared to field observations, are discussed.